2012
DOI: 10.21273/jashs.137.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Floral Longevity in Impatiens walleriana

Abstract: Impatiens (Impatiens walleriana) are currently among the most valuable and widely cultivated floriculture crops in the world. Attractive floral display is a primary goal for breeders of impatiens. Although breeders have selected for this trait, little consideration has been given to floral longevity as a means to increase the floral display of bedding crops. In this study, 259 commercial inbred lines of impatiens were grown in a greenhouse and evaluated for floral longevity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…Fewer studies have explored the heritability of intact floral longevity, which would be more directly relevant to the evolution of floral longevity in wild species. Of those, two demonstrated significant additive genetic effects underlying variation in intact floral longevity (Krahl & Randle, ; Howard et al ., ), while a third showed that postharvest floral longevity is positively correlated to intact floral longevity in at least one species (Martin & Stimart, ). Thus, from this limited evidence, we know that a response to selection on floral longevity is possible in at least some horticultural species.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have explored the heritability of intact floral longevity, which would be more directly relevant to the evolution of floral longevity in wild species. Of those, two demonstrated significant additive genetic effects underlying variation in intact floral longevity (Krahl & Randle, ; Howard et al ., ), while a third showed that postharvest floral longevity is positively correlated to intact floral longevity in at least one species (Martin & Stimart, ). Thus, from this limited evidence, we know that a response to selection on floral longevity is possible in at least some horticultural species.…”
Section: Introductionmentioning
confidence: 99%
“…También es importante la resistencia a factores bióticos y abióticos, éste último con el desarrollo de la tolerancia al sol (Uchneat, 2007). Entre las investigaciones en mejoramiento clásico se destaca el estudio de Howard et al (2012), quienes realizaron cruzamientos dialelicos para estimar la habilidad combinatoria general y específica de 259 líneas para la longevidad floral.…”
Section: Fitomejoramiento Convencionalunclassified
“…En los materiales usados en este experimento se encontró una disminución extremadamente baja de los genes ACS1, ACS2 y ACO1, los cuales se relacionan con la síntesis de ácido 1-aminociclopropano-1-carboxílico (ACC) y de la ACC oxidasa (ACO), precursores de etileno (Tanase y Otsu, 2013). La disminución en la concentración de etileno se ha registrado en muchos cultivos incluyendo I. walleriana (Howard et al, 2012;Olsen et al, 2015). Por otra parte, se ha registrado casos en los que por hibridación inter e intraespecífica se ha logrado obtener también plantas menos sensibles al etileno (Macnish et al, 2004).…”
Section: Longevidad Floralunclassified